Pemahaman Preskripsi Dokter (Formula Magistralis dan Spesialitis) untuk Anak oleh Dokter Muda Fakultas Kedokteran Universitas Gadjah Mada - Tri Murini, Sri Suharmi, Heri Wijanarko (Berita Kedokteran Masyarakat (BKM), 2003)
Background: One of the teaching activities on medical pharmaceutical science includes imparting the knowledge of proper way of describing a certain kind of medicine. Objective: The objective of the study is to discover the extent of the students' success in understanding the taught material.Method: It is a cross-sectional study, adapting 140 medical students' as subyect and medical prescriptions for kid patients as obyect. The students' ability to understand medical prescriptions is descriptively analyzed. The drug elements analyzed include drug ingredients, method of dosage estimate, dosage form and regimen. The gold standard was the researcher understanding.Result: The result of the study into the medical students' analysis of the doctor's prescriptions indicates that the extent of accuracy achieved by the subyect, in the specifications of drug prescribed, is 56,05% for the description, 63,06% for dosage estimation method, 94,90% for dosage form, and 73,23% for dosage regimen. As to the patent drug, the subyect reported 91,75% for the description, 69,07% for dosage estimation method, 89,90% for dosage form and 67,01% for dosage regimen.Conclusion: As the study has revealed, the subyect well understood the elements of the formula of the specification of the drug prescribed. However, they did poorly in the method of drug description and the drug dosage estimate for kid patients. Concerning the patent drug, the medical students' competence in the understanding of the elements of the formula was satisfactory except for the drug dosage estimation. Keywords: doctor's prescription, medical student